Thiosemicarbazones and selected tyrosine kinase inhibitors synergize in pediatric solid tumors: NDRG1 upregulation and impaired prosurvival signaling in neuroblastoma cells - Krchniakova, Maria; Paukovcekova, Silvia; Chlapek, Petr; Neradil, Jakub; Skoda, Jan; Veselska, Renata (Frontiers in Pharmacology, 2022)
Tyrosine kinase inhibitors (TKIs) are frequently used in combined therapy to enhance treatment efficacy and overcome drug resistance. The present study analyzed the effects of three inhibitors, sunitinib, gefitinib, and lapatinib, combined with iron-chelating agents, di-2-pyridylketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT) or di-2-pyridylketone-4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC). Simultaneous administration of the drugs consistently resulted in synergistic and/or additive activities against the cell lines derived from the most frequent types of pediatric solid tumors. The results of a detailed analysis of cell signaling in the neuroblastoma cell lines revealed that TKIs inhibited the phosphorylation of the corresponding receptor tyrosine kinases, and thiosemicarbazones downregulated the expression of epidermal growth factor receptor, platelet-derived growth factor receptor, and insulin-like growth factor-1 receptor, leading to a strong induction of apoptosis. Marked upregulation of the metastasis suppressor N-myc downstream regulated gene-1 (NDRG1), which is known to be activated and upregulated by thiosemicarbazones in adult cancers, was also detected in thiosemicarbazone-treated neuroblastoma cells. Importantly, these effects were more pronounced in the cells treated with drug combinations, especially with the combinations of lapatinib with thiosemicarbazones. Therefore, these results provide a rationale for novel strategies combining iron-chelating agents with TKIs in therapy of pediatric solid tumors.